THE INFLUENCE OF LIQUID COMPLEX FERTILIZERS (LCF 3:18:18) ON YIELD AND QUALITY OF CHINESE CABBAGE - Dydiv О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Chinese cabbage is demanding on soil fertility, as well as provision of macro- and microelements. A high yield of Chinese cabbage is obtained on fertile, loamy soils, the pH is close to neutral. Due to a violation of the balance of mineral substances in the soil and a lack of moisture, plants lag behind in growth. In ecological terms, liquid complex fertilizers (LCF 3:18:18), which are easily absorbed by plants, are the effective mineral fertilizers. The studies on the influence of different rates of liquid complex fertilizers (LCF 3:18:18) on the yield and biochemical composition of Chinese cabbage were conducted in the conditions of the Western Forest Steppe of Ukraine on dark grey podzolic light loamy soils. The subject of the research was a hybrid of Chinese cabbage called Enduro F1. The scheme of the experiment included the following veriants: 1) Control (without fertilizers); 2) LCF – 40 l/ha; 3) LCF – 80 l/ha; 4) LCF – 120 l/ha; 5) LCF – 160 l/ha; 6) LCF – 200 l/ha. For three years of the research, a large length (27 and 30 cm), long width (13-14 sm) and weight of heads (1000 and 1100 g), density of 8 and 9 points, were obtained on the variants with LCF – 160 l/ha and LCF – 200 l/ha, while in the control version (without fertilizers) these figures were the lowest and amounted for 19.9 cm and 600 g respectively. Having applied the field-seeded method of growing Chinese cabbage using the liquid complex mineral fertilizer (LCF 3:18:18) at the rate of 120 l/ha (LCF) and 160 l/ha (LCF), one obtained the high yielding capacity of Chinese cabbage heads (74,2 and 84,6 t/ha), which exceeds the control (without fertilizers – 49.4 t/ha) by 24.8 and 35.4 l/ha respectively. It was found that the increased rates of liquid complex fertilizers (LCF 3:18:18) of 200 l/ha did not contribute to a significant increase in yielding capacity. Liquid complex mineral fertilizers (LCF 3:18:18) improved the quality of Chinese cabbage heads, in particular, one obtained the highest content of dry matter (8.56 %), total sugar (2.72 %), ascorbic acid (32.8 mg/%), protein (1.84 %) in version 4 at (LCF) the rate of 120 l/ha. The content of nitrate nitrogen in all variants of the experiment did not exceed the maximum permissible concentration (MPC). There is a suggestion to apply a liquid complex mineral fertilizer (LCF 3:18:18) at the rate of 160 l/ha) in order to obtain a high yielding capacity with good quality of Chinese cabbage heads of the Enduro F1 hybrid. One should apply the field-seeded method of cultivation on dark grey podzolic soils in the Western Forest Steppe of Ukraine.